2017
DOI: 10.1080/14686996.2017.1377590
|View full text |Cite
|
Sign up to set email alerts
|

Energy conversion in magneto-rheological elastomers

Abstract: Magneto-rheological (MR) elastomers contain micro-/nano-sized ferromagnetic particles dispersed in a soft elastomer matrix, and their rheological properties (storage and loss moduli) exhibit a significant dependence on the application of a magnetic field (namely MR effect). Conversely, it is reported in this work that this multiphysics coupling is associated with an inverse effect (i.e. the dependence of the magnetic properties on mechanical strain), denoted as the pseudo-Villari effect. MR elastomers based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…In inhomogeneous magnetic fields [18], even larger deformations become possible; elongations of several hundred percent have been observed in MAE specimens [19][20][21]. Very recently, other magnetoelastic effects related to MS, the Villary effect [22,23] and the Wiedemann effect [24], have been reported in compliant (mechanically soft) MAE materials as well.…”
Section: Introductionmentioning
confidence: 99%
“…In inhomogeneous magnetic fields [18], even larger deformations become possible; elongations of several hundred percent have been observed in MAE specimens [19][20][21]. Very recently, other magnetoelastic effects related to MS, the Villary effect [22,23] and the Wiedemann effect [24], have been reported in compliant (mechanically soft) MAE materials as well.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple experiments performed on MRE have resulted in a significant collection of research data pointing to a strong relationship between the rheological characteristics of the material and magnetic field. Partly, the results were obtained from studies on damping devices [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] or from investigations dedicated to the magnetorheological effect [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. For instance, influenced by a field of 0.8 T, a silicone and carbonyl iron-based sample initially polymerized in a field of 1.5 T demonstrated an increase of its shear modulus (G′) from 0.25 to 2.5 MPa [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Measured at 0.8 T, the loss-factors were found to be 0.15 for a sample with no orientation and 0.20 for an oriented specimen; however, strengthening of the field caused increasing of this parameter. Relative 60% variations in the case of rigid elastomer and more than 470% variations in the case of soft elastomer were observed on increasing the external field from 0 to 0.5 T [ 39 ]. In addition, the authors of [ 40 ] found out that composites containing particles with diameters of 20 and 100 µm exhibited relative MR effects of 30 and 60% in a magnetic field of 225 mT.…”
Section: Introductionmentioning
confidence: 99%
“…The Villari effect in magnetorheological elastomers has been recently studied [31,32]. In these studies, the Villari signal obtained when a magnetic field is applied to the sample has been fitted to a second-order polynomial approximation.…”
Section: Resultsmentioning
confidence: 99%